CRIMINAL-LEGAL ENSURING OF FREEDOM OF RELIGION IN MODERN CONDITIONS:: A COMPARATIVE ANALYSIS - Ya. Lykhova, Sophia; D. Leonov, Borys; D. Lysko, Tetiana; K. Shaptala, Natalya; I. Maksymov, Sergiy (Revista Gênero e Interdisciplinaridade, 2021)
The article conducts a comparative criminal law research of ensuring freedom of religion in Ukraine and in some foreign countries. International standards for the protection of religious freedom are analyzed. It is concluded that this right is fundamental and should be ensured at the appropriate level by all states of the civilized world. The object of the study is the right of a person to freedom of religion guaranteed by the Constitution of Ukraine. In carrying out this research, a comparative legal method was widely used, which allowed for a two-level analysis (empirical and theoretical) of legal systems of Ukraine and some foreign countries in terms of ensuring freedom of religion by criminal law, to identify original and specific manifestations of such support, to determine the patterns of development of criminal legislation of individual countries and to establish relations with international standards for the protection of religious freedom. In addition, a formal-legal method was used, which made it possible to classify and systematize the researched criminal law norms, and a method of interpretation, which allowed to clarify the content of certain norms of criminal law. As a result of the research, some gaps and advantages of domestic legislation in terms of criminal law ensuring the right to freedom of religion were identified, it is established that the modern criminal law of Ukraine in general meets international standards for the protection of the constitutional right of citizens to freedom of religion, but there are some shortcomings in terms of unambiguous understanding of the elements of crimes that infringe on freedom of religion. This makes it difficult to apply the law. In particular, there are a significant number of evaluative features of the corpus delicti that need to be clarified and cannot be clearly defined by a literal interpretation of the criminal law.